Implikasi Value Added Intellectual Capital Terhadap Financial Company’s Performance - Ekadjaja, Margarita; Ekadjaja, Agustin; Siswanto, Halim Putera (Manajemen Bisnis Kompetensi, 2019)
Economic developments are increasingly complex, raising issues in research in the field of intellectual capital. The company’s ability to be competent in competition does not only lead to ownership of real assets but rather leads to new discoveries in managing the organization and human resources of the company. This study analyzes intellectual capital (as an independent variable) and financial company’s performance (as the dependent variable, namely Return On Assets, Return On Equity and Asset Turnover), on banking companies listed on the Indonesia Stock Exchange for 3 years (2015-2017). The differentiator of this research with previous research is the addition of measuring the ratio of company activity in evaluating company performance. The subject of banking companies is because the banking industry is one of the most intensive sectors of intellectual capital. The purpose of this study was to analyze the implications of value added intellectual capital on a company’s financial performance as measured by Return on Assets, Return on Equity, and Assset Turnover. After knowing the variables of value added intellectual capital that have implications for the company’s financial performance, it can be used as a basis for the company in an effort to increase the value of the firm. Based on partial testing, Value Added of Intellectual Capital has a significant positive effect on Return on Assets and Return on Equity, but a negative and not significant effect on Asset Turnover.Keywords: Intellectual Capital, Return On Asset, Return On Equity, Asset Turnover